IMPLEMENTATION OF POPULATION INFORMATION SYSTEM AS A BASIC FOR DECISION MAKING IN GAMPONG MEURANDEH ACEH, LANGSA CITY - Dewi Rosa Indah; Muhammad Salman; Rahmad Tantawi (Global Science Society, 2022)
This community service activity was carried out in Gampong Meurandeh Aceh, Langsa Lama District, Langsa City which aims to overcome problems faced by the partners of the Government of Gampong Meurandeh Aceh, related to population data. A common problem that occurs with partners is that most of the residents of the Meurandeh Aceh village are poor people who are included in the category of recipients of direct cash assistance or zakat recipients, who often have problems in disbursing due to invalid population data. To overcome this problem, the service team offers a solution to design a web-based Population Information System application product, whose function is to assist population data management in Gampong Meurandeh Aceh. The implementation of this trial is for 4 months, with the method of providing training to the staff of the Aceh Geuchik Meurandeh Office in using this application.